H9N2 influenza virus spillover into wild birds from poultry in China bind to human‐type receptors and transmit in mammals via respiratory droplets. Issue 2 (9th March 2021) - Zhang, Xinghai; Li, Yuanguo; Jin, Song; Wang, Tiecheng; Sun, Weiyang; Zhang, Yiming; Li, Fangxu; Zhao, Menglin; Sun, Leiyun; Hu, Xinyu; Feng, Na; Xie, Ying; et al.
Abstract: H9N2 influenza virus has been reported worldwide for several decades, and it has evolved into multiple genotypes among domestic poultry. However, the study involving ecology and evolution of low pathogenic avian influenza virus H9N2 in wild birds in China is limited. Here, we carried out surveillance of avian influenza virus H9N2 in wild birds along with the East Asian–Australian migratory flyway in China in 2017. To estimate the prevalence of H9N2 avian virus in wild birds, information on exposure of wild bird populations to H9N2 viruses using serology, in addition to virology, would greatly improve monitoring capabilities. In this study, we also present serological data of H9N2 among wild birds in China during 2013–2016. We report the identification of poultry‐derived H9N2 isolates from asymptomatic infected multispecies wild birds such as Common kestrel ( Falco tinnunculus ), Northern goshawk ( Accipiter gentilis ), Little owl ( Athene noctua ) and Ring‐necked Pheasant ( Phasianus colchicus ) in North China in June 2017. Phylogenetic analysis demonstrated that Tianjin H9N2 isolates belong to the G81 and carry internal genes highly homologous to human H10N8 and H7N9. The isolates could directly infect mice without adaptation but were restricted to replicate in the respiratory system. Glycan‐binding preference analyses suggested that the H9N2 isolates have acquired a binding affinity for the human‐like receptor. Notably, results from transmission experiment in guinea pigs and ferrets demonstrated the wild birds‐derived H9N2 influenza virus exhibits efficient transmission phenotypes in mammalian models via respiratory droplets. Our results indicate that the H9N2 AIVs continued to circulate extensively in wild bird populations and migratory birds play an important role in the spread and genetic diversification of H9N2 AIVs. The pandemic potential of H9N2 viruses demonstrated by aerosol transmission in mammalian models via respiratory droplets highlights the importance of monitoring influenza viruses in these hosts.